STRATEGI PENGELOLAAN SUMBER DAYA MANUSIA PADA PROYEK KONSTRUKSI VILLA DI PROVINSI BALI - I Putu Krisna Yudha; Ni Made Ary Widiastini Widiastini; Putu Indah Rahmawati (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2023)
This study aims to analyze human resource management strategies in the province of Bali. The research locations were conducted in 2 project locations, namely the Ubud Lodtunduh Villa Development Project in Gianyar Regency, and the BaliHandara Villa Project in Buleleng Regency. The sample of this research is 15 project workers. The research method is carried out with a qualitative approach. Data collection in this study was carried out by means of observation, in-depth interviews, and documentation. The results of the study show (1) HR management of construction projects is carried out by controlling and supervising work implementation and carrying out structured project organizational planning (2) Factors that can accelerate project completion, namely by increasing the number of workers and applying overtime hours